2021
DOI: 10.32604/cmc.2021.018514
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Method for Covid-19 Detection Using Light Weight Convolutional Neural Network

Abstract: The COVID-19 pandemic is a significant milestone in the modern history of civilization with a catastrophic effect on global wellbeing and monetary. The situation is very complex as the COVID-19 test kits are limited, therefore, more diagnostic methods must be developed urgently. A significant initial step towards the successful diagnosis of the COVID-19 is the chest X-ray or Computed Tomography (CT), where any chest anomalies (e.g., lung inflammation) can be easily identified. Most hospitals possess X-ray or C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…From the studies indicated in Table 7 it is visible that, 61.9% of the studies have achieved more than 95% accuracy. The models used in these studies are ResNet-50 [56] , VGG-16 [56] , [72] , VGG-19 [70] , CapsNet [88] , DensNet121 [75] , MobileNet [82] , MobileNetV2 [83] , InceptionV3 [83] , Xception [83] , InceptionResNetV2 [82] and CNNs developed from scratch [6] , [105] , [107] , [108] , [129] . From this analysis, it can be seen that among the studies that have achieved more than 95% accuracy values, only 38.5% of studies have come up with newly developed CNN architectures.…”
Section: Discussion and Lessons Learnedmentioning
confidence: 99%
See 2 more Smart Citations
“…From the studies indicated in Table 7 it is visible that, 61.9% of the studies have achieved more than 95% accuracy. The models used in these studies are ResNet-50 [56] , VGG-16 [56] , [72] , VGG-19 [70] , CapsNet [88] , DensNet121 [75] , MobileNet [82] , MobileNetV2 [83] , InceptionV3 [83] , Xception [83] , InceptionResNetV2 [82] and CNNs developed from scratch [6] , [105] , [107] , [108] , [129] . From this analysis, it can be seen that among the studies that have achieved more than 95% accuracy values, only 38.5% of studies have come up with newly developed CNN architectures.…”
Section: Discussion and Lessons Learnedmentioning
confidence: 99%
“…Only the study done by Bekhet et al. [129] has not used a GPU, since they mainly focused on building an efficient method that even can run on a normal CPU. Thus, it can be observed that many recent studies have used GPUs for their implementation.…”
Section: Discussion and Lessons Learnedmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic continues to pose several challenges to medical systems worldwide, and the ability to make quick clinical choices is critical [ 48 ]. Predictive machine learning algorithms that analyze medical images and estimate risk are pretty valuable.…”
Section: Literature Surveymentioning
confidence: 99%
“… [36] , Alqudah, Qazan and Alqudah [37] , Chakraborty, Dhavale and Ingole [38] , Karakanis and Leontidis [39] , Bekhet et al. [40] ; Huang and Liao [41] developed lightweight CNNs using Chest X-ray images based COVID-19 detection. Zebin and Rezvy [42] , Nayak et al.…”
Section: State-of-the-artmentioning
confidence: 99%